Antifungal Catheter Lock Therapy for the Management of a Persistent Candida albicans Bloodstream Infection in an Adult Receiving Hemodialysis. Issue 7 (30th April 2014) - Paul DiMondi, V.; Townsend, Mary L.; Johnson, Melissa; Durkin, Michael
<x xml:space="preserve">Abstract</x> Antifungal catheter lock therapy (AfLT) with liposomal amphotericin B has been used in the treatment of pediatric central line infections caused by Candida species; however, reports describing the use of liposomal amphotericin B lock therapy in the adult hemodialysis patient population are lacking. Management of central line–associated candidemia with systemic therapy alone is often challenging due to the propensity of Candida species to form biofilms on foreign bodies. We describe a 64‐year‐old woman who was receiving hemodialysis 3 times/week and was hospitalized with persistent fungemia. Despite receiving intravenous micafungin, she had multiple positive blood cultures for Candida albicans, which finally cleared after 7 days. Her double‐lumen catheter was considered the most likely nidus of infection. Although catheter removal would have been preferred, this was not possible given her vasculopathy, history of multiple bloodstream infections, and lack of other available sites for vascular access. Catheter exchange was performed, and liposomal amphotericin B AfLT was administered in combination with intravenous micafungin for a total of 6 days. During this time, the patient experienced no discernible adverse effects secondary to AfLT. At discharge, AfLT was discontinued, and intravenous micafungin was changed to oral fluconazole. After 6 months of treatment, the patient remained culture negative and maintained her dialysis access. To our knowledge, this is the first case report of liposomal amphotericin B catheter lock therapy used to manage a persistent C. albicans bloodstream infection in an adult receiving hemodialysis. AfLT is a novel concept for treating catheter‐associated fungal infections. Liposomal amphotericin B was chosen based on its favorable in vitro activity against Candida species biofilms in catheter lock environments. We identified several barriers to implementing AfLT, and these issues may prohibit the use of AfLT. This case report illustrates the benefits and challenges of managing catheter‐associated fungal infections with AfLT. Further study is required to examine the efficacy, safety, and feasibility of this approach.